2021
DOI: 10.1016/j.nicl.2021.102635
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain disconnectivity mapping of post-stroke fatigue

Abstract: Highlights We tested for associations between post stroke fatigue (PSF) and both lesion characteristics and brain structural disconnectome in 84 S patients. Results provided no evidence supporting a simple association between PSF severity and lesion characteristics or disconnectivity. PSF was strongly correlated with depression. Further studies including patients with more severe symptoms are needed to generalize the findings across a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 88 publications
1
26
0
2
Order By: Relevance
“…However, we did not find associations between structural network connectivity and chronic PSF. These results are in line with findings in the general stroke population showing no associations between chronic PSF and structural network measures or lesion characteristics ( 44 ). A recent study showed that the functional connectivity of the fronto-striato-thalamic network could predict the response for PSF treatment with modafinil ( 15 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, we did not find associations between structural network connectivity and chronic PSF. These results are in line with findings in the general stroke population showing no associations between chronic PSF and structural network measures or lesion characteristics ( 44 ). A recent study showed that the functional connectivity of the fronto-striato-thalamic network could predict the response for PSF treatment with modafinil ( 15 ).…”
Section: Discussionsupporting
confidence: 91%
“…Lesion network mapping is an approach that combines traditional lesion-symptom mapping approaches with functional connectivity information derived from large normative 'connectome' datasets to evaluate lesion associated networks. This approach has been useful for uncovering network correlates of a number of lesion syndromes that have been historically challenging to 'localize' [21][22][23][24] but has not been applied to time orientation to date.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating complex microstructural brain connectome information based on 7T diffusion MRI tractography data from healthy controls, the current disconnectome approach, utilizing T2-lesion masks to create individual brain disconnectivity maps, has provided new insights into different brain disorders, yet the neuroaxonal correlates have not been investigated ( Foulon et al, 2018 , Thiebaut de Schotten et al, 2020 , Ulrichsen et al, 2021 ). Here we provide a link between imaging-based and biologically-assessed axonal damage.…”
Section: Discussionmentioning
confidence: 99%